Collaborative virtual 3D environment for internet-accessible physics experiments - Scheucher, B.; Bayley, P.; Guetl, Christian; Harward, J. (International Association of Online Engineering, 2009)
Immersive 3D worlds have increasingly raised the interest of researchers and practitioners for various learning and training settings over the last decade. These virtual worlds can provide multiple communication channels betweeen users and improve presence and awareness in the learning process. Consequently virtual 3D environments facilitate collaborative learning and training scenarios. In this paper we focus on the integration of internet-accessible physics experiments (iLabs) combined with the TEALsim 3D simulation toolkit in project Wonderland, Sun's toolkit for creating collaborative 3D virtual worlds. Within such a collaborative environment these tools provide the opportunity for teachers and students to work together as avatars as they control actual equipment, visualize physical phenomenon generated by the experiment, and discuss the results. In particular we will outline the steps of integration, future goals, as well as the value of a collaboration space in Wonderland's virtual world.